2021
DOI: 10.4103/ijd.ijd_1088_20
|View full text |Cite
|
Sign up to set email alerts
|

Can Dermoscopy and Ultrasonography be Considered a Prognostic Tool in Management of Psoriasis?

Abstract: Background: Dermoscopy can reliably predict the diagnosis of plaque psoriasis. Ultrasonography has been increasingly used in dermatology in inflammatory diseases like psoriasis as a tool for evaluation. Hence, this study was done to evaluate the role of dermoscopy and ultrasonography as prognostic aid in plaque psoriasis. Aims and Objectives: To study the sonographic and dermoscopic findings of clinically diagnosed psoriatic lesions and the changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 9 publications
0
7
0
5
Order By: Relevance
“…[69][70][71] Moreover, the distribution density of the dotted/ globular vessels decreased gradually until there was a partial return to normal. 72,73 The clinical symptom score shown a significant correlation with the diameter of the glomus observed under dermoscopy, 74 which suggested that the changes in the vascular pattern in the skin lesions may be used as an index to observe the effect of psoriasis treatment and the recovery of skin lesions.…”
Section: Assessment Of Therapeutic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…[69][70][71] Moreover, the distribution density of the dotted/ globular vessels decreased gradually until there was a partial return to normal. 72,73 The clinical symptom score shown a significant correlation with the diameter of the glomus observed under dermoscopy, 74 which suggested that the changes in the vascular pattern in the skin lesions may be used as an index to observe the effect of psoriasis treatment and the recovery of skin lesions.…”
Section: Assessment Of Therapeutic Effectmentioning
confidence: 99%
“…The dynamic observation of patients with psoriasis who had been cured, showed that, with the improvement of clinical symptoms, the diameter of the dilated glomus under dermoscopy decreased gradually 69–71 . Moreover, the distribution density of the dotted/globular vessels decreased gradually until there was a partial return to normal 72,73 . The clinical symptom score shown a significant correlation with the diameter of the glomus observed under dermoscopy, 74 which suggested that the changes in the vascular pattern in the skin lesions may be used as an index to observe the effect of psoriasis treatment and the recovery of skin lesions.…”
Section: Assessment Of Therapeutic Effect and Severitymentioning
confidence: 99%
“…Łuszczyca to ogólnoustrojowa choroba zapalna skóry o przewlekłym charakterze, której manifestacje skórne są efektem hiperproliferacji naskórka [10]. Postawienie diagnozy następuje zwykle na podstawie introduction Dermoscopy, also known as epiluminescence microscopy, is a non-invasive technique for imaging melanocytic lesions commonly used in the diagnosis of skin cancers [1,2].…”
Section: łUszczycaunclassified
“…Therefore, dermoscopy seems to be an effective and quick examination facilitating the diagnosis without the need to perform a skin biopsy, which is a procedure that generates additional costs and causes discomfort to patients [9]. psoriAsis Psoriasis is a systemic, inflammatory skin disease of a chronic nature, skin manifestations of which are the result of hyperproliferation of the epidermis [10]. The diagnosis is usually made on the basis of the clinical picture, i.e., red papules and silvery scales, however, dermoscopy is a useful complementary examination [7,10].…”
Section: łUszczycamentioning
confidence: 99%
See 1 more Smart Citation